Pendidikan Kesehatan Relaksasi Akupresur Bagi Remaja - Ayu Aminatussyadiah; Rhadika Wahyu Kurnia Ningrum; Adelia Ika Cahyani (Jurnal Pengabdian Bidang Kesehatan, 2026)
Health education is an effort or attempt to provide information to improve individual abilities in making decisions related to health and health-related skills, especially for adolescents. This activity aims to increase the knowledge of SMKS BIM students about acupressure for adolescents. The counseling activity was carried out on May 26, 2026 with 43 students aged between 15-18 years old, using the pretest-posttest method with leaflet media, powerpoint presentations and practicing with students. The results showed an increase in student knowledge from 70 to 95 after being given education. The majority of students aged 16 years (middle adolescents) were identified as having a risk of physical health problems. The education and mentoring provided to students/me were able to increase their knowledge about the benefits and techniques of acupressure to deal with the health problems they experienced. The counseling method with lectures and leaflet media was proven to be easy for students/me to understand and could improve their skills in acupressure practice.